Circulating microRNAs are a potential molecular link between nutrition and colorectal cancer risk in Lynch Syndrome - Kärkkäinen, Minta (2023)
Lynch syndrome is an inherited cancer-predisposing syndrome where occur mutations in mismatch repair genes. Colorectal cancer is a common form of cancer within Lynch syndrome carriers. The inherited gene mutation predisposes to the development of colorectal cancer, but diet, especially red meat, fiber, and calcium intake, is known to significantly impact cancer development. Currently, there is limited information on what kind of molecular mechanisms mediate the effect of nutrition on colorectal cancer risk within Lynch syndrome carriers. Recent studies have indicated the importance of circulating non-coding RNAs, like microRNAs, in cancer development. Circulating microRNAs are small approximately 20 nucleotide long molecules in the bloodstream that regulate several biological processes. Circulating microRNA expression patterns change in connection with cancer. This thesis aimed to study whether red meat, fiber, and calcium daily intake are associated with circulating microRNA expression levels of Lynch syndrome carriers. The associations between nutrient intake and circulating microRNA expression levels were studied using the Spearman rank correlation coefficient and multiple linear regression analysis. The statistical tests revealed significant associations between these variables where hsa-miR-3613-5p was specifically associated with red meat intake and hsa-miR-144-5p with fiber intake. The possible function of hsa-miR-3613-5p and hsa-miR-144-5p in colorectal cancer was studied by transfecting appropriate microRNA mimics in patient-derived colorectal cancer organoids and by performing cell viability and apoptosis assays to the transfected cells. Hsa-miR-144-5p reduced the viability of colorectal cancer cells and in addition induced apoptosis in these cells. Hsa-miR-3613-5p had no clear effect on the viability of the studied cancer cells. The study suggests nutrition has an impact on circulating microRNA expression levels. In addition, these microRNAs associated with diet may enhance or suppress colorectal cancer cell growth.